Organellar Introns in Fungi, Algae, and Plants - Jigeesha Mukhopadhyay; Georg Hausner (Cells, 2021)
Introns are ubiquitous in eukaryotic genomes and have long been considered as ‘junk RNA’ but the huge energy expenditure in their transcription, removal, and degradation indicate that they may have functional significance and can offer evolutionary advantages. In fungi, plants and algae introns make a significant contribution to the size of the organellar genomes. Organellar introns are classified as catalytic self-splicing introns that can be categorized as either Group I or Group II introns. There are some biases, with Group I introns being more frequently encountered in fungal mitochondrial genomes, whereas among plants Group II introns dominate within the mitochondrial and chloroplast genomes. Organellar introns can encode a variety of proteins, such as maturases, homing endonucleases, reverse transcriptases, and, in some cases, ribosomal proteins, along with other novel open reading frames. Although organellar introns are viewed to be ribozymes, they do interact with various intron- or nuclear genome-encoded protein factors that assist in the intron RNA to fold into competent splicing structures, or facilitate the turn-over of intron RNAs to prevent reverse splicing. Organellar introns are also known to be involved in non-canonical splicing, such as backsplicing and trans-splicing which can result in novel splicing products or, in some instances, compensate for the fragmentation of genes by recombination events. In organellar genomes, Group I and II introns may exist in nested intronic arrangements, such as introns within introns, referred to as twintrons, where splicing of the external intron may be dependent on splicing of the internal intron. These nested or complex introns, with two or three-component intron modules, are being explored as platforms for alternative splicing and their possible function as molecular switches for modulating gene expression which could be potentially applied towards heterologous gene expression. This review explores recent findings on organellar Group I and II introns, focusing on splicing and mobility mechanisms aided by associated intron/nuclear encoded proteins and their potential roles in organellar gene expression and cross talk between nuclear and organellar genomes. Potential application for these types of elements in biotechnology are also discussed.